Temporal Courses in EEG Theta and Alpha Activity in the Dynamic Health Qigong Techniques Wu Qin Xi and Liu Zi Jue - Henz, Diana; Schöllhorn, Wolfgang I. (Frontiers in Psychology, 2018)
Health Qigong is a common technique of Traditional Chinese Medicine applied to strengthen mental and physical health. Several studies report increases in EEG theta and alpha activity after meditative Qigong techniques indicating a relaxed state of mind. To date, little is known on the effects of dynamic Health Qigong techniques that comprise bodily movements on brain activity. In the current study, we compared effects of two dynamic Health Qigong techniques on EEG brain activity. Subjects performed the techniques Wu Qin Xi (five animals play) and Liu Zi Jue (six healing sounds) in a within-subjects design. Eyes-open and eyes-closed resting EEG was recorded before and immediately after each 15-minute practice block. Additionally, the Profile of Mood States (POMS) questionnaire was administered at pretest, and after each 15-minute practice block. Results show a decrease in alpha activity after 15 minutes, followed by an increase after 30 minutes in the Health Qigong technique Liu Zi Jue. Theta activity was decreased after 15 minutes, followed by an increase after 30 minutes in the technique Wu Qin Xi. Results of the POMS indicated an increased vigor-activity level with decreased fatigue and tension-anxiety levels in both techniques after 30 minutes of practice. Our results demonstrate different temporal dynamics in EEG theta and alpha activity for the Health Qigong techniques Wu Qin Xi and Liu Zi Jue. We hypothesize that the found brain activation patterns result from different attentional focusing styles and breathing techniques performed during the investigated Health Qigong techniques.